Analisis Wacana Kritis Pengajuan Gugatan Badan Kemenangan Nasional (Bpn) Ke Mahkamah Konstitusi (Mk) Pada Artikel Media Daring Tirto.Id - Azzahra Maulida Tantri Goserira (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
Pemilu become one of the best time for the media to voice issues to the public. Behind the news, the media is trying to build discourse to be enjoyed by the wider community. This study raises the reporting of the newspaper with the theme